2012
DOI: 10.1002/nme.4391
|View full text |Cite
|
Sign up to set email alerts
|

An augmented Lagrangian technique combined with a mortar algorithm for modelling mechanical contact problems

Abstract: SUMMARY A finite element formulation for three dimensional (3D) contact mechanics using a mortar algorithm combined with a mixed penalty–duality formulation from an augmented Lagrangian approach is presented. In this method, no penalty parameter is introduced for the regularisation of the contact problem. The contact approach, based on the mortar method, gives a smooth representation of the contact forces across the bodies interface, and can be used in arbitrarily curved 3D configurations. The projection surfa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
26
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 35 publications
0
26
0
Order By: Relevance
“…For contact algorithms based on Lagrangian finite elements such methods can be found in e.g. [36,[41][42][43][44] and within IGA in [12,13]. Using these methods based on a standard Lagrange multiplier interpolation, a system of increased size containing both displacement and Lagrange multiplier degrees of freedom has to be solved.…”
Section: Dual Basis Functionsmentioning
confidence: 99%
“…For contact algorithms based on Lagrangian finite elements such methods can be found in e.g. [36,[41][42][43][44] and within IGA in [12,13]. Using these methods based on a standard Lagrange multiplier interpolation, a system of increased size containing both displacement and Lagrange multiplier degrees of freedom has to be solved.…”
Section: Dual Basis Functionsmentioning
confidence: 99%
“…Numerical tests showed that this choice gives a better condition number of the iteration matrix than other choices [10]. Eventually, different sets of values of r, k can be used for the normal and for the tangential parts.…”
Section: Augmented Lagrangian Formulationmentioning
confidence: 96%
“…At each contact element, the restrictions to the element facets of the integrals needed for the computation of the weight factors n 1 AB , n 2 AB are evaluated. The weight factors are then obtained by assembling the contributions of all elements [10,53].…”
Section: Contact Element Definitionmentioning
confidence: 99%
See 2 more Smart Citations